"Category‐6" supertyphoon Haiyan in global warming hiatus: Contribution from subsurface ocean warming. Issue 23 (2nd December 2014) - Lin, I.‐I.; Pun, Iam‐Fei; Lien, Chun‐Chi
Abstract With the extra‐ordinary intensity of 170 kts, supertyphoon Haiyan devastated the Philippines in November 2013. This intensity is among the highest ever observed for tropical cyclones (TCs) globally, 35 kts well above the threshold (135kts) of the existing highest category of 5. Though there is speculation to associate global warming with such intensity, existing research indicate that we have been in a warming hiatus period, with the hiatus attributed to the La Niña‐like multi‐decadal phenomenon. It is thus intriguing to understand why Haiyan can occur during hiatus. It is suggested that as the western Pacific manifestation of the La Niña‐like phenomenon is to pile up warm subsurface water to the west, the western North Pacific experienced evident subsurface warming and created a very favorable ocean pre‐condition for Haiyan. Together with its fast traveling speed, the air‐sea flux supply was 158% as compared to normal for intensification.